Youths and consumption of news via Internet and social media - Catalina-García, Beatriz; García Jiménez, Antonio; Montes Vozmediano, Manuel (Historia y Comunicación Social, 2015)
The aim of this paper is to analyze the habits of young people in relation to consumption of news on the Internet, in a scenario where social media has a strong presence. A survey of Spanish university students focused on, on the one hand, on the intensity of access and, secondly, on gender, is carried out in relation to the frequency of news access, the specialization of journalistic information, the motivation to read news, the news verifying and the perception about impartiality and credibility. This exploratory research has revealed the growing importance of social media as a source for access to news.